Revisión especial al departamento de recaudación y su incidencia en los resultados económicos en la empresa electrica pública estratégica cnel ep, regional Guayas Los Ríos sistema Quevedo, periodo 2012. - Torres Pisco, Jorge Luis (2015)
The Superintendence of revenues collected by the Electric Company Strategic Public CNEL EP Guayas Regional Los Rios, emits the necessary administrative arrangements to collect in the different points, after the verification of the information systems and computer system that applies the Quevedo on the basis of the provisions of the managers of CNEL EP failed to check that the company has maintained the efficiency, efficacy and effectiveness of operational level during the period 2012. The policies of an administrative nature that emit the highest authorities of the company, allow us to measure on a monthly basis the level of tax collection that keeps the company, which in the consolidated is 92.22 %; these levels of collection, demonstrate that the company conforms to permanent administrative policies that maintains the company for the collection and constantly seeks to achieve the operational excellence to achieve raise in a 100 % of the invoiced value on a monthly basis…..